Mapping the Influence of Business Phrases on the Effectiveness of Digital Marketing Communication: A Systematic Literature Review - Suningsih, Sri; Putri, Lidya Ayuni; Nurbaiti, Syarifah; Waziana, Winia (Reflection Journal, 2026)
This study aims to systematically map the trends, themes, and conceptual developments in research examining the influence of business phrases on the effectiveness of digital marketing communication over the period 2015–2025. A Systematic Literature Review (SLR) approach was employed following the PRISMA 2020 guidelines. A total of 366 articles were initially identified from major academic databases, including Scopus, Web of Science, ScienceDirect, Taylor & Francis, and SpringerLink. After a rigorous screening and eligibility process, 41 articles were selected for in-depth analysis. The findings reveal a significant increase in scholarly attention to the integration of business linguistics and digital communication, particularly after 2020. Bibliometric and thematic analyses identify four dominant research themes: (1) the pragmatic functions of business phrases in digital communication, (2) their influence on consumer perception, (3) their role in enhancing audience engagement, and (4) cross-cultural linguistic adaptation. The conceptual synthesis demonstrates that business phrases act as strategic linguistic elements that mediate the relationship between message construction and consumer behavior through cognitive and affective mechanisms. Furthermore, cross-cultural adaptation serves as a moderating factor influencing communication effectiveness. This study contributes theoretically by proposing an integrated conceptual model linking language, persuasion, and digital communication effectiveness. Practically, the findings provide valuable insights for practitioners in designing more persuasive, adaptive, and evidence-based digital marketing communication strategies.